Phenotypic and genomic assessment of the potential threat of human spaceflight-relevant Staphylococcus capitis isolates under stress conditions - Siems, Katharina; Runzheimer, Katharina; Rehm, Anna; Schwengers, Oliver; Heidler von Heilborn, David; Kaser, Liv; Arndt, Franca; Neidhöfer, Claudio; Mengel, Jan Philipp; Parcina, Marijo; Lipski, André; Hain, Torsten; et al. (Frontiers in Microbiology, 2022)
Previous studies have reported that spaceflight specific conditions such as microgravity lead to changes in bacterial physiology and resistance behavior including increased expression of virulence factors, enhanced biofilm formation and decreased susceptibility to antibiotics. To assess if spaceflight induced physiological changes can manifest in human-associated bacteria, we compared three spaceflight relevant Staphylococcus capitis isolates (DSM 111179, ISS; DSM 31028, clean room; DSM 113836; artificial gravity bedrest study) with the type strain (DSM 20326T). We tested the three strains regarding growth, colony morphology, metabolism, fatty acid and polar lipid pattern, biofilm formation, susceptibility to antibiotics and survival in different stress conditions such as treatment with hydrogen peroxide, exposure to desiccation, irradiation with X-rays and UV-C. Moreover, we sequenced, assembled and analyzed the genomes of all four strains. Potential genetic determinants for phenotypic differences were investigated by comparative genomics. We found that all four strains show similar metabolic patterns and the same susceptibility to antibiotics. All four strains were considered resistant to fosfomycin. Physiological differences were mainly observed compared to the type strain and minor differences among the other three strains. The ISS isolate and the bedrest study isolate exhibit a strong delayed yellow pigmentation, which is absent in the other two strains. Pigments were extracted and analyzed via UV/Vis spectroscopy showing characteristic carotenoid spectra. The ISS isolate showed the highest growth rate as well as weighted average melting temperature (WAMT) of fatty acids (41.8 °C) of all strains. The clean room isolate showed strongest biofilm formation and a high tolerance to desiccation. In general, all strains survived desiccation better in absence of oxygen. There were no differences among the strains regarding radiation tolerance. Phenotypic and genomic differences among the strains observed in this study are not inevitably indicating an increased virulence of the spaceflight isolate. However, the increased growth rate, higher WAMT and colony pigmentation of the spaceflight isolate are relevant phenotypes that require further research within the human spaceflight context. We conclude that combining genetic analysis with classical microbiological methods allows the detailed assessment of the potential threat of bacteria in highly regulated and extreme environments such as spaceflight environments.